Assessing Arabic Language Exposure Instrument (I-Alex) In Higher Education Using The Rasch Measurement Model - Nur Afiqah Athirah Awwad Mohd Rushdi; Lily Hanefarezan Asbulah; Firuz-Akhtar Lubis; Ashinida Aladdin; Mus’ab Sahrim (Department of Arabic Language Education, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Indexed by WOS